2016
DOI: 10.3847/0004-637x/818/1/8
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Magnetic Fields Derived From Simultaneous Microwave and Euv Observations and Comparison With the Potential Field Model

Abstract: We estimated the accuracy of coronal magnetic fields derived from radio observations by comparing them to potential field calculations and the differential emission measure measurements using EUV observations. We derived line-of-sight components of the coronal magnetic field from polarization observations of the thermal bremsstrahlung in the NOAA active region 11150, observed around 3:00 UT on 2011 February 3 using the Nobeyama Radioheliograph at 17 GHz. Because the thermal bremsstrahlung intensity at 17 GHz i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…Radio spectral observations of type III bursts, spike structures associated with type IV bursts and zebra patterns could also provide estimates of the magnetic field in the coronal source regions of the radio emission [21][22][23]. In addition, when the emission mechanisms are known, microwave imaging at one or more frequencies could be used to produce maps of the coronal magnetic field strength in limited regions [24][25][26][27][28][29]. More recently, the phenomenon of magnetic-fieldinduced transition (MIT) [30] has caught the attention of the solar physics community, and theoretical and laboratory investigations have demonstrated the potential of MIT lines in measurements of the coronal magnetic field [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Radio spectral observations of type III bursts, spike structures associated with type IV bursts and zebra patterns could also provide estimates of the magnetic field in the coronal source regions of the radio emission [21][22][23]. In addition, when the emission mechanisms are known, microwave imaging at one or more frequencies could be used to produce maps of the coronal magnetic field strength in limited regions [24][25][26][27][28][29]. More recently, the phenomenon of magnetic-fieldinduced transition (MIT) [30] has caught the attention of the solar physics community, and theoretical and laboratory investigations have demonstrated the potential of MIT lines in measurements of the coronal magnetic field [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, on the other hand, we find the underestimation of B IMF by the PFM. The underestimation of the B by the PFM has been recently reported also from simultaneous microwave and Extreme-Ultra Violet (EUV) observations [14]. They found that the line-of-sight B observed in the lower solar corona is 2 ∼ 5.4 times larger than B calculated from the PFM and raised a question to the current-free assumption of the PFM in the photosphere and chromosphere.…”
Section: Resultsmentioning
confidence: 87%
“…Recently, Kallunki et al (2020) reported the first successful solar polarization observations at 3 and 13 mm carried out with the Aalto University Metsähovi Radio Telescope. Figures 1-3 provide the examples of the most recent observations, obtained with the NoRH (Iwai and Shibasaki, 2013;Miyawaki et al, 2016) and with the RATAN-600 (Kaltman, 2019). Iwai and Shibasaki (2013) derived the coronal and chromospheric magnetic fields in the active region NOAA 11455 from the circular polarization observations at 17 GHz and spectral observations at 17 and 34 GHz obtained by NoRH on April 13, 2012 (Figure 1).…”
Section: Selected Observational Examplesmentioning
confidence: 99%
“…An example of the successful separation of the two components is presented in Miyawaki et al (2016). For analysis of the active region NOAO 11150, the authors selected a part of the active region consisting of coronal loops and only weak chromospheric magnetic field, and combined the circular FIGURE 2 | (a) 171A image of AR NOAO 11150 observed with SDO/AIA on February 2, 2011 with the overlaid outward (white) and inward (black) magnetic field lines from the potential field extrapolation.…”
Section: Selected Observational Examplesmentioning
confidence: 99%